Analysis of time-averaged secondary flow cells in wide and narrow straight open channels with lateral bed deformation - Chattopadhyay, T.; Kundu, S. (Archives of Mechanics, 2023)
The usual cellular pattern of the time averaged secondary flow circulation in the central section of wide open channels shows a distorted (laterally or vertically) structure due to the changes in bed configurations along lateral direction. The structures of these secondary circulations (under different bed configurations) are crucial for different types of hydraulic modeling. This study presents mathematical models of the time averaged secondary velocities (lateral and vertical components) for a turbulence-induced secondary current at the central section of a wide open-channel flow under different types of elevated and non-elevated bed conditions. Starting with the Reynolds Averaged Navier-Stokes equation and using the continuity equation, at first the governing equation of secondary flow velocity is obtained including the effects of the eddy viscosity and viscosity of the fluid. The model equations is solved using a separation of the variable technique imposing the bed perturbation condition. Full analytical solutions are achieved through mathematical analysis using suitable boundary conditions consistent with experimental observations. Initially the models are derived for a non-elevated bedforms comprised of alternating equal widths of smooth and rough bed strips. These models are modified further for bedforms with unequal widths of rough and smooth bed strips and elevated periodic bed structures. Four different types of elevated bed configurations are investigated and a general approach is suggested for other types of bed forms. All the proposed models are validated with existing experimental results to ensure the applicability and in each cases, improved results are observed. Obtained results show that the centre of circulation of the cellular structure occurs above the junction of the rough and smooth bed strips (consistent with experimental observations) and it gradually shifts towards the smooth strip, when the length of the rough bed strip is increased. The shifting as a function shows a non-linear pattern with the length of the rough bed strip. A least-square model is proposed to identify the circulation center as a function of the ratio of rough to smooth bed strips. It is also found that the vertically distorted secondary cells are generated when the bed slope strictly increase/decrease throughout the length of the one whole circulation. Finally, all the proposed models are compared with an existing model and an error analysis is done. Results of error analysis show that the present study can be more suitable as it yields improved results.